Financial Derivatives / Hedging with Futures, Forwards, Options and Swaps - Winstone David (International Thomson Business Press, 1995)
This book introduces the role of financial derivatives - futures, forwards, options and swaps - in treasury risk management. Acknowledgements, Introduction, The Nature of Currency Exposure, Internal Hedging Techniques, Currency Borrowing or Currency Deposits, The Foreign Exchange Market, Forward Exchange Contracts, Interest Rate Risk Exposure, Forward/ Forwards, Forward or Future Rate Agreements (FRAs), An Introduction to Futures, Interest Rate Futures, Currency Futures, Advanced Futures Concepts, An Introduction to Traded Options, Currency Options, Interest Rate Options, Option Pricing, Interest Rate Swaps, Currency Swaps, Summary and Conclusions, Postscript - Barings Bank, Index.